THE EFFECT OF FINANCIAL REPORTING QUALITY AND GOOD CORPORATE GOVERNANCE ON INFORMATION ASYMETRY IN BANKING COMPANIES LISTED ON THE IDX - Iqlima Azhar (Fakultas Ekonomi Universitas Samudra, 2021)
The purpose of this study was to examine the effect of financial reporting quality and good corporate governance on information asymmetry. The population of this research is the banking companies listed on the Indonesia Stock Exchange (BEI) in the 2010-2019 period totaling 43 banks and the samples in this study were 7 companies. The sampling technique used purposive sampling method. Data were analyzed using SPSS with the data analysis method used, namely the classical assumption test and hypothesis testing such as multiple linear regression, individual parameter significant test (partial test), simultaneous significance test (simultaneous test) and determination coefficient test (R2). The result of the multiple linear regression equation is Y = 0.860 + 0.058X2 - 0.065X3 + e. The results showed that partially the quality of financial reporting had no significant effect on information asymmetry and good corporate governance had a significant effect on information asymmetry, but simultaneously financial reporting quality and good corporate governance had a significant effect on information asymmetry.